Portuguese women as wine consumers - the impact of beliefs on the option to drink wine - Pereira, H.; Salgueiro, M.F.; Marques, S. (International Conference on Business and Economic Develpoment, 2017)
Purpose - The main purpose of this study is to identify the conditioning factors, main influences and/or barriers (attributes, personal attitudes or society pressure) of the decision of having wine instead of any other alcoholic beverage outside meals. Design/Methodology/Approach - The target of the study is the Portuguese female consumer. Two focus groups were conducted in order to identify the most important beliefs. A structured questionnaire was then used for data collection and 215 valid answers were obtained from Portuguese female wine consumers (those drinking wine at least once per month). Findings - The socio-demographic characteristic age plays a crucial role and the results show that two distinct groups of female consumers should be considered. The younger consumers (ages 18 to 34) perceive wine as alcohol, an alternative to other alcoholic beverages. The evaluation of personal beliefs (such as impact on health, alcohol percentage control, or the possibility of avoiding “mixing alcohols”) has a high impact on their consumption frequency – the better they perceive wine, the higher is their intention and frequency of wine consumption outside meals. The older consumers (ages 45 to 64) envisage wine as culture. For them wine is mostly a drink to be taken along with a meal, with the sophistication and refinement it deserves. Excesses, which are strongly “embodied” on the out of meal consumption, are penalized both socially (negative third party opinion) and personally (negative own impression). Practical Implications – The research results provide an important insight into wine companies can pursuit and use different communication approaches in order to get specific segments. Originality/Value - These results allow for a better understanding of customer specificities, with practical actions aimed at their real needs and expectations.